ANALISIS INVESTASI PERKEBUNAN SAWIT UNTUK KELAYAKAN INVESTASI PADA PT. AMP PLANTATION - Neldi, Mondra (Jurnal Ekobistek, 2014)
Abstract - The author conducted research on a company enganged in oil palm Plantation are in PT. AMP Plantation. The purpose of this study to determine whether an investment in PT. AMP Plantation feasible when analyzed by the method Accounting Rate of Return, Payback Period, dan Net Present Value. Financially based on the method used, namely with rate 12 % discount NPV method, the investment activities of palm oil mills (MCC) capacity of 30 tonnes of FFB per hour is not feasible to be implemented with NPV value (-Rp. 10.480.259.666.416) and Payback period for 12 years and 6 months. While the ARR method, the investment activities of oil palm feasible, with value obtained ARR of 32 %. The total investment needed is Rp. 15.235.723.500.146 Based on the plantation area and total production of FFB as has been recommended by the government?s policies to tacklee environmental problems, ideally PT. AMP Plantation takes environmental cost and social cost for a capacity of 30 tonnes FFB/ hour. To Protect smallholder farmers, local governments should form a regional government-owned (public enterprises) for the development of oil palm plantations (MCC) with the consideration of land area and capital owned by smallholders. Field Key : investment, oil palm Plantation